Microplastics in Yellow River Delta wetland: Occurrence, characteristics, human influences, and marker. (March 2020) - Duan, Zhenghua; Zhao, Shuang; Zhao, Lejun; Duan, Xinyue; Xie, Sen; Zhang, Hai; Liu, Yubin; Peng, Yawen; Liu, Chunguang; Wang, Lei
Abstract: Microplastics (MPs) are widespread in the environment including coastal wetlands. The influence of different types and intensities of human activities on the occurrence of MPs in coastal wetlands is still unknown. The aim of this study was to investigate the distribution of MPs and the contribution of human activities in different areas of Yellow River Delta wetland. MPs were widely detected in different areas of the wetland even in the protection area with little human activities. Direct human activities resulted in more severe MPs contamination in the protection area than the tourism area. In the soil of different areas, the MPs abundances ranged from 136 to 2060 items/kg. The concentrations of polyethylene terephthalate (PET) ranged from 536 to 660 μg/kg, and the concentrations of polycarbonate (PC) ranged from 83.9 to 196 μg/kg. The MP abundances of the three areas had significant correlations with PET concentrations. These results indicate that the direct influence of human activities has much greater contribution than indirect influence. These results also suggest that PET concentration can be used as a potential marker of MPs contamination in wetland soils. Graphical abstract: Image 1 Highlights: MPs were widely presented in the protection area of wetland with little human activities. Direct human activities result in more severe MPs contamination in the protection area than the tourism area. The concentrations of polyethylene terephthalate (PET) in the wetland soil ranged from 536 to 660 μg/kg. The concentrations of polycarbonate (PC) in the wetland soil ranged from 83.9 to 196 μg/kg. The PET concentration can be used as a potential marker of MPs contamination.